The Effect of Progressive Muscle Relaxation on Depression and Anxiety among Postpartum Mothers in Semarang - Azzahro Diniar Adhani; Niken Sukesi (International Journal Of Health Science, 2026)
Mothers often face psychological issues during the postpartum phase, such as depression and anxiety, which can impact the health and development of their children. Complementary therapy in the form of progressive muscle reactivity (PMR) is a non-pharmacological strategy to reduce depression and anxiety. The purpose of this study was to investigate how progressive muscle reactivity affects postpartum maternal anxiety and grief in two community health centers (Puskesmas) and several hospitals in Semarang City. Using a quantitative approach, this research design captured pre-installation and post-installation patterns. Purposive sampling was used to select 50 respondents for the study sample. The Edinburgh Postnatal Depression Scale (EPDS) was used to measure depression, and the Generalized Anxiety Disorder-7 (GAD-7) was used to measure anxiety. The Wilcoxon test was used to analyze the data. Based on the results of the progressive muscle reactivity technique, there was a significant decrease in depression and anxiety (p = 0.0005, p < 0.05). Seventy-six percent indicated that their anxiety had reached a satisfactory level, while 36 percent indicated that their decisions had decreased. Thus, it can be said that progressive muscular connection makes people more resilient and reduces anxiety. In medical settings, this treatment is recommended as a complementary intervention to improve patients' psychological well-being.